2011
DOI: 10.1074/jbc.m111.240002
|View full text |Cite
|
Sign up to set email alerts
|

Atomic Force Microscopy of Connexin40 Gap Junction Hemichannels Reveals Calcium-dependent Three-dimensional Molecular Topography and Open-Closed Conformations of Both the Extracellular and Cytoplasmic Faces

Abstract: Atomic force microscopy was used to study the three-dimensional molecular topography and calcium-sensitive conformational changes of Connexin40 hemichannels (connexons) reconstituted in 1,2-dioeloyl-sn-glycero-3-phosphatidylcholine lipid bilayers. Two classes of objects were observed that differed in their protrusion heights above the bilayer (2.6 versus 4.2 nm). Comparison to reconstituted connexons containing Connexin40 truncated to eliminate most of its C-terminal cytoplasmic domain showed that the two heig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
32
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(38 citation statements)
references
References 30 publications
6
32
0
Order By: Relevance
“…The resolution of hemichannel structure is not high enough to decipher individual subunits of hexameric channels2025. However, the AFM images show distinct pores and surrounding subunits, the outer and inner diameters similar to published data2025.…”
Section: Discussionsupporting
confidence: 67%
“…The resolution of hemichannel structure is not high enough to decipher individual subunits of hexameric channels2025. However, the AFM images show distinct pores and surrounding subunits, the outer and inner diameters similar to published data2025.…”
Section: Discussionsupporting
confidence: 67%
“…The relative insensitivity of Cx40 gap junctions to the Ca 2ϩ /CaM gating mechanism suggests that atrial gap junctions may not close as completely in response to Ca 2ϩ overload conditions, which may be relevant to atrial fibrillation. The apparent insensitivity of Cx40 gap junctions to uncoupling by hundreds of nanomolar cytosolic [Ca 2ϩ ] in this study does not preclude blockade by submillimolar or millimolar [Ca 2ϩ ], as evidenced by the closing of Cx40 hemichannels in the presence of 3.6 mM Ca 2ϩ (3). The decline in Cx43 G j was inhibited by the omission of external CaCl 2 or pretreatment with the CaM inhibitor CDZ (Figs.…”
Section: Discussionmentioning
confidence: 79%
“…More recent studies, using atomic force microscopy (AFM) [23], reviewed by Sosinsky and Nicholson [24], showed that 0.5 mM Ca 2+ decreased the diameter of the extracellular entrance of Cx26 hemichannels from ~15 Å to ~6 Å. Conformational changes were also observed at the intracellular entrance of the pore, but these were more difficult to interpret as a consequence of the flexibility of the cytoplasmic surface, a feature subsequently confirmed by calculation of the temperature factors of the Cx26 crystal structure [10] and MD simulation [11]. More recently, Lal and co-workers reported Ca 2+ induced conformational changes at both the intracellular and extracellular entrance to Cx40 channels [25]. The original EM and subsequent AFM studies suggest that Ca 2+ gating involves substantial conformational changes of the entire channel.…”
Section: Conformational Changes Mediated By Extracellular Calcium mentioning
confidence: 97%